Bilateral Gluteal Ischemic Necrosis Mistaken for Stage IV Pressure Wound: Case Report and Discussion. Issue 2 (March 2015) - Simman, Richard; Reynolds, David
Abstract : BACKGROUND: Sacral and gluteal pressure wounds are a common problem in elderly and critically ill patients. Prompt and accurate diagnosis is important to determine the best plan of treatment. CASE: A 48-year-old female was hospitalized with severe trunk pain and bilateral necrotic gluteal wounds present for more than 1 year initially diagnosed as stage IV pressure ulcers; she reported pain radiating to her lower extremities. She had multiple comorbid conditions, including peripheral vascular disease, smoking, and hypertension. CONCLUSION: Wound care providers should be aware of this differential diagnosis especially in patients with history of vascular disease.